2019
DOI: 10.1029/2019jd031282
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Subtropical Highs on Summertime Precipitation in North America

Abstract: Numerous observational studies have found that the Hadley cells are expanding poleward in both the Northern and Southern Hemispheres, and model results suggest that such expansion is likely to continue throughout this century as a result of global warming. This has led to concerns that the subtropical dry zones may also shift poleward. However, precipitation changes associated with Hadley cell width are zonally asymmetric—especially in the Northern Hemisphere—suggesting that a more regional focus may give a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…The North Pacific High Intensity index shown in Fig. 1b is based on the North Pacific Subtropical High (NPSH) strength index developed by Schmidt et al 44 , which measures the average monthly mean NCEP Reanalysis 2 SLP in a 10 × 10 box centered on the NPSH SLP centroid. See ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The North Pacific High Intensity index shown in Fig. 1b is based on the North Pacific Subtropical High (NPSH) strength index developed by Schmidt et al 44 , which measures the average monthly mean NCEP Reanalysis 2 SLP in a 10 × 10 box centered on the NPSH SLP centroid. See ref.…”
Section: Methodsmentioning
confidence: 99%
“…See ref. 44 for more details. We then show anomalies of this index (hPa) relative to a 1982-2018 climatology in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Both approaches reveal that zonal mean widening does not imply a widening at all longitudes. For example, the southeastern United States, though in the subtropical belt, is removed from the prototypical Hadley cell-wise circulation (Staten et al 2019); there, shifts in the North Atlantic subtropical high modulate large-scale precipitation patterns (Schmidt and Grise 2019).…”
Section: E901mentioning
confidence: 99%
“…Previous studies have shown that the NASH affects precipitation in the SE US on timescales that range from diurnal to multi‐decadal (e.g., Diem, 2006; Li et al ., 2011, 2012, 2013; Bishop et al ., 2019; Schmidt and Grise, 2019). On daily timescales, Luchetti et al .…”
Section: Introductionmentioning
confidence: 99%
“…On multi‐decadal timescales the NASH western ridge has been shown to have shifted westward between 1948 and 1977 (Li et al ., 2011) and eastward from 1978–2007 (Diem, 2013a; 2013b). Some of this variability has been linked to the influence of stationary wave trains driven by the Pacific Decadal Oscillation (Li et al ., 2011; 2013) as well as to a possible intensification and expansion of the NASH during this period (Li et al ., 2011; He et al ., 2017; Schmidt and Grise, 2019).…”
Section: Introductionmentioning
confidence: 99%